Fossil-fueled development (SSP5): An energy and resource intensive scenario for the 21st century. (January 2017) - Kriegler, Elmar; Bauer, Nico; Popp, Alexander; Humpenöder, Florian; Leimbach, Marian; Strefler, Jessica; Baumstark, Lavinia; Bodirsky, Benjamin Leon; Hilaire, Jérôme; Klein, David; Mouratiadou, Ioanna; Weindl, Isabelle; et al.
Highlights: The SSP5 scenarios mark the upper end of the scenario literature in fossil fuel use, food demand, energy use and greenhouse gas emissions. The SSP5 marker scenario results in a radiative forcing pathway close to the highest Representative Concentration Pathway (RCP8.5).. An investigation of mitigation policies in SSP5 confirms high socio-economic challenges to mitigation in SSP5. In SSP5, ambitious climate targets require land based carbon management options such as avoided deforestation and bioenergy production with CCS. The SSP5 scenarios provide useful reference points for future climate change, impact, adaption, mitigation and sustainable development analysis. Abstract: This paper presents a set of energy and resource intensive scenarios based on the concept of Shared Socio-Economic Pathways (SSPs). The scenario family is characterized by rapid and fossil-fueled development with high socio-economic challenges to mitigation and low socio-economic challenges to adaptation (SSP5). A special focus is placed on the SSP5 marker scenario developed by the REMIND-MAgPIE integrated assessment modeling framework. The SSP5 baseline scenarios exhibit very high levels of fossil fuel use, up to a doubling of global food demand, and up to a tripling of energy demand and greenhouse gas emissions over the course of the century, marking the upper end of the scenario literature in several dimensions. These scenarios are currently the only SSP scenarios that result in a radiative forcing pathway as high as the highest Representative Concentration Pathway (RCP8.5). This paper further investigates the direct impact of mitigation policies on the SSP5 energy, land and emissions dynamics confirming high socio-economic challenges to mitigation in SSP5. Nonetheless, mitigation policies reaching climate forcing levels as low as in the lowest Representative Concentration Pathway (RCP2.6) are accessible in SSP5. The SSP5 scenarios presented in this paper aim to provide useful reference points for future climate change, climate impact, adaption and mitigation analysis, and broader questions of sustainable development.